Visualizing the Collaborative Problem Solving Process in an Immersive Cross Platform Game - Thompson, Meredith; Bilgin, Cigdem Uz; Eberhart, Rik; Cho, Lucy; Anteneh, Melat; Klopfer, Eric (2021 7th International Conference of the Immersive Learning Research Network (iLRN), 2021)
This study explores how players engage in problem solving during a cross-platform collaborative learning game about cellular biology. We tested the game with 8 pairs of students: 2 pairs of middle school students, 2 pairs of high school students, and 4 pairs of students in a biotechnology workforce program. Players took on one of two roles: An Explorer in virtual reality head mounted display and a Navigator using a tablet. Players took on one of two roles: An Explorer in virtual reality head mounted display and a Navigator using a tablet. Videos of 40-minute game play sessions for 8 pairs of players were transcribed and examined for patterns of game play based on stages of collaborative problem solving (CPS) developed by Fiore et al (2017). Players' discussion during gameplay was analyzed and visualized through Epistemic Network Analysis. Results suggested that players engaged in two-way communication using biology terms throughout the game, and that communication styles were linked to roles. After initial orientation, players moved through multiple cycles of clue finding and discussion that followed similar patterns even in groups with different knowledge levels. These results suggest that collaborative problem solving can be initiated through roles in a serious game and documented through participants' conversation during a serious game. Future research will focus on whether the game can be used to learn, practice, and improve players' CPS skills.